2020
DOI: 10.1186/s12864-020-07015-w
|View full text |Cite
|
Sign up to set email alerts
|

Tracing key genes associated with the Pinctada margaritifera albino phenotype from juvenile to cultured pearl harvest stages using multiple whole transcriptome sequencing

Abstract: Background Albino mutations are commonly observed in the animal kingdom, including in bivalves. In the black-lipped pearl oyster Pinctada margaritifera, albino specimens are characterized by total or partial absence of colouration resulting in typical white shell phenotype expression. The relationship of shell colour with resulting cultured pearl colour is of great economic interest in P. margaritifera, on which a pearl industry is based. Hence, the albino phenotype provides a useful way to exa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 66 publications
0
4
0
Order By: Relevance
“…It has been reported that biomineralization is closely related to shell pigmentation, sequential layer-by-layer mineralization is directed by cells at the edge of the mantle tissues, and pigments in the periostracum layer are produced by the mantle ( Xu et al, 2019 ). In Pinctada margaritifera , multiple transcriptome analysis supports the involvement of biomineralization genes in the process of shell pigmentation ( Auffret et al, 2020 ). The shell mineralization process involves energy metabolism and organic matrix crystallization ( Zhao et al, 2019 ; Zhao et al, 2020 ; He et al, 2021 ).…”
Section: Discussionmentioning
confidence: 98%
“…It has been reported that biomineralization is closely related to shell pigmentation, sequential layer-by-layer mineralization is directed by cells at the edge of the mantle tissues, and pigments in the periostracum layer are produced by the mantle ( Xu et al, 2019 ). In Pinctada margaritifera , multiple transcriptome analysis supports the involvement of biomineralization genes in the process of shell pigmentation ( Auffret et al, 2020 ). The shell mineralization process involves energy metabolism and organic matrix crystallization ( Zhao et al, 2019 ; Zhao et al, 2020 ; He et al, 2021 ).…”
Section: Discussionmentioning
confidence: 98%
“…There are studies that white-shell oysters could employ endocytosis to downregulate Notch levels and lead to melanoblasts apoptosis, preventing pigmentation [ 82 ]. In addition to this, Notch-related genes (Delta, Jagged-2, E3 ubiquitin-protein ligase) are upregulated in the albino juvenile phenotype in Pinctada margaritifera ( P. margaritifera ) [ 86 ].…”
Section: Functional Roles Of Notch Signaling Pathway Members In Inver...mentioning
confidence: 99%
“…The Notch signaling pathway, an evolutionarily conserved cell signaling system, functions in a great diversity of biological processes such as cell proliferation and growth, cell fate determination, differentiation, and stem cell maintenance (Artavanis-Tsakonas et al, 1999;Bray, 2006). Recently, the Notch pathway has been proposed to play a crucial role in shell formation and pigmentation in molluscs, including pearl oysters (Pinctada margaritifera and P. fucata martensii) (Jiao et al, 2019;Auffret al, 2020), the clam (Meretrix meretrix) (Yue et al, 2015), and the Pacific oyster (Feng et al, 2015). Here, we first detected that this pathway underwent significant selection in different Pacific oyster populations, and some core genes of the pathway, i.e., Notch1 (two in GLD, one in XST, and one in QD) and Notch2 (one in GLD and one in QD and XST), were involved.…”
Section: Selected Signatures Related To Habitat Adaptation Of the Pac...mentioning
confidence: 99%